2020
DOI: 10.1111/jcmm.15507
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cell‐derived factors promote the colonization of collagen 3D scaffolds with human skin cells

Abstract: The development of stem cell technology in combination with advances in biomaterials has opened new ways of producing engineered tissue substitutes. In this study, we investigated whether the therapeutic potential of an acellular porous scaffold made of type I collagen can be improved by the addition of a powerful trophic agent in the form of mesenchymal stromal cells conditioned medium (MSC‐CM) in order to be used as an acellular scaffold for skin wound healing treatment. Our experiments showed that MSC‐CM su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…As shown in Figure 4C, after 4 h of incubation, PKH67-labeled exosomes were readily taken up by the dermal fibroblasts. In a previous study [7], our group obtained similar results for complete MSC-derived conditioned medium, suggesting that this is a characteristic of the whole MSC secretome. showing the uptake of PKH67-labeled exosomes by dermal fibroblasts.…”
Section: Msc-derived Exosomes Stimulate Proliferation and Migration Of Human Keratinocytes And Dermal Fibroblastssupporting
confidence: 75%
See 3 more Smart Citations
“…As shown in Figure 4C, after 4 h of incubation, PKH67-labeled exosomes were readily taken up by the dermal fibroblasts. In a previous study [7], our group obtained similar results for complete MSC-derived conditioned medium, suggesting that this is a characteristic of the whole MSC secretome. showing the uptake of PKH67-labeled exosomes by dermal fibroblasts.…”
Section: Msc-derived Exosomes Stimulate Proliferation and Migration Of Human Keratinocytes And Dermal Fibroblastssupporting
confidence: 75%
“…In recent years, the therapeutic application of bone marrow-derived mesenchymal stromal/stem cells (MSCs) shifted from cellular transplantation to acellular therapy, in light of a novel mechanism of action, based on the favorable effects of factors secreted by these cells. Previous work, including our own, supports the use of MSC conditioned medium (CM) for skin wound healing, on account of its stimulative properties on several key biological processes such as proliferation, migration, and angiogenesis [4][5][6][7][8][9]. Besides growth factors and cytokines, the CM (the secretome) also includes the ubiquitous large family of extracellular vesicles (EVs) comprising exosomes, microvesicles (microparticles), and apoptotic bodies.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Many authors already proved MSC ability to secrete proepithelizing mediators and recently MSC‐derived factors have also been shown to promote the colonization of collagen‐based 3D scaffolds with human skin cells 24 . Latter data seem to confirm this role for MSC‐CM in promoting the adherence of keratinocytes and fibroblasts as well as keratinocyte proliferation in collagen‐based scaffolding materials 42 . Those studies also demonstrated the induction of a prohealing phenotype in fibroblasts cultured on collagen scaffold in the presence of MSC‐CM.…”
Section: Discussionmentioning
confidence: 99%